Cultivating Resilience: Revitalizing the Gayam Tree Ecosystem as a Green Belt for Landslide Mitigation - I Wayan Suwendra; I Wayan Karyasa; Putu Indah Rahmawati; I Nyoman Laba Jayanta; Gede Hendri Ari Susila; I Luh Meiyana Aris Susanti (International Journal of Community Service Learning, 2026)
Landslide-prone hilly areas become increasingly vulnerable when slope vegetation degradation is not balanced with strengthening community capacity in environmentally based disaster mitigation. This community service program revitalizes the green belt through the Gayam Tree Ecosystem (GTE) concept as a non-structural disaster-mitigation strategy, and strengthens community capacity in Pegayaman Village, Buleleng. The Participatory Action Research (PAR) approach was implemented with the Kumpi Bukit Tourism Group (Pokdarwis) to collaboratively design, implement, and evaluate interventions. The initial implementation phase involved planting 168 gayam trees, with a survival rate of ±90%, in a hilly landscape of ±1,584 ha. Strengthening governance was supported by SIM-Gayam (≥300 geo-tagging points) for spatial monitoring, as well as 12 route signs along two trekking routes (10 km and 5 km) to support conservation education. The involvement of 50 participants demonstrated a shift from ceremonial participation to community ownership through data-driven maintenance and reporting practices. Initial results confirm the complementarity of local vegetation and social capacity within an eco-DRR framework and provide a baseline for longitudinal evaluation toward the 5,000-tree target. These findings offer a model for replicating community-based mitigation for at-risk hillside villages in North Bali.